Krause’s accessory lacrimal gland dacryops - case report and literature review - Alsulaiman, Hamad M.; Fatani, Dalal R.; Al Sheikh, Osama; Elkhamary, Sahar; Maktabi, Azza; Alkatan, Hind M.; Schellini, Silvana Artioli [UNESP] (Taylor & Francis, 2020)
The authors are describing two rare cases of dacryops involving the Krause accessory lacrimal glands and affecting the orbit. In both cases, the lesion was located in the inferior fornix, with no preceding trauma, surgery or trachomatous conjunctival scarring. The first case involved a clear orbital extension with evidence of optic nerve compression. The second case extended from the anterior orbit to the limbus. Both had surgical removal with good outcome. As Krause gland dacryops are similar to other orbital cysts, clinical, imaging and histopathologic evaluation are essential to confirm the final diagnosis.
Keywords: Accessory lacrimal gland; dacryops; Krause